Класстан тыс жумысларда үлке материалларынан пайдаланыўдың тәлим –тәрбиялық әҳмийети (SCIENCE and SOCIETY, 2019)
This article is about the educational and moral meaning of using archaeological findings in extracurricular work. There is given an analysis to the kinds and methods of using regional materials in extracurricular work. The author of the article emphasizes the positive